Gender, womens health care concerns and other social factors in health and health care - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2018)
This volume of 'Research in the Sociology of Health Care' analyses micro-level gender issues and other social factors impacting macro-level health care systems. Examining the health and health care issues of patients and providers of care both in the United States and in other countries, chapters focus on linkages to policy and population concerns as ways to meet global health care needs.